Phytochemical constituents and biological activities of Clausena excavata Burm. F., Micromelum minutum (G. Forst.) Wight & Arn. and Melicope latifolia (DC.) T.G. Hartley (Rutaceae) - Lim, Pei Cee (2020)
The Rutaceae family has been used in traditional medicine practices to treat various ailments such as snake bites, fever, cough and diarrhoea. Clausena excavata, Micromelum minutum and Melicope latifolia are plants of the Rutaceae family grown locally in Malaysia. To date, there are limited studies on the activity of their extracts and compounds on antimicrobial activity against oral pathogenic bacteria, antioxidant capacity especially cellular antioxidant activity as well as cytotoxicity properties. Therefore, this study aimed to investigate the phytochemical constituents, antimicrobial, antioxidant and cytotoxicity properties of C. excavata, M. minutum and M. latifolia. A total of 24 compounds including one new conjugated sesquiterpene were isolated from C. excavata, M. minutum and M. latifolia using different chromatographic techniques. Structural elucidation was achieved by means of spectroscopic and spectrometric analysis. Phytochemical investigation on stem bark of C. excavata yielded four coumarins (dentatin (166), nordentatin (54), clausenidin (64) and xanthoxyletin (66)), three alkaloids (heptazoline (51), clausine H (167) and heptaphylline (67)), together with clausenarin (168). Atranorin (170), a polyketide and lichexanthone (171), a xanthone were also first isolated from the Clausena species. Flavonoids namely araneosol (173), 5-hydroxyauranetin (172) and 5,7-dihydroxy-3,8,4’-trimethoxyflavone (174) together with stigmasterol (169) were isolated from the leaves of M. minutum. Meanwhile, M. latifolia leaves afforded one new conjugated sesquiterpene, trivially named as amelicarin (176) together with nine known compounds consist of sterol derivatives (β-sitosterol (175), β-sitostenone (178), stigmast-4-ene-6β-ol-3-one (179), stigmast-4-ene-3,6-dione (177)), four flavonoid glycosides (quercetin 3-O robinobioside (181), kaempferol 3-O-rutinoside (182), kaempferol 3-O-glucoside (183), kaempferol 3-O-arabinoside (184)) and one flavonoid (taxifolin (180)). These compounds are first reported from the species M. latifolia. Disc diffusion antimicrobial assay against S. mutans and E. faecalis revealed the potency of hexane, ethyl acetate extracts and three compounds from C, excavata together with all extracts from M. minutum and M. latifolia against S. mutans. Further antimicrobial evaluation by determining the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) indicated that C. excavata hexane extract showed the lowest MIC and MBC values 0.31 and 0.63 mg/mL respectively towards S. mutans. However, the selected compounds from C. excavata (clausine H, heptazoline and nordentatin) showed insignificant inhibition towards S. mutans suggested that the activity of the extracts could be due to synergistic effect of the compounds present in the hexane extract of C. excavata. None of the extracts and their isolated compounds showed significant activity towards E. faecalis. This is the first report in which the plant extracts and selected compounds were tested against S. mutans and E. faecalis. Plant extracts were evaluated using chemical antioxidant assays as well as assessing their phenolic contents. All the methanol extracts showed high antioxidant capacities in all the assays where methanol extract from C. excavata exhibited potent activity based on DPPH, FRAP and CUPRAC assays while M. minutum and M. latifolia displayed relative higher activity with trolox equivalent values exceeded 1900 mg TE/g extract in TEAC and 2000 μmol TE/g extract in ORAC. Meanwhile, cellular antioxidant activity assay (CAA) of methanol extract of M. latifolia displayed highest activity (52.33 ± 1.53%) while taxifolin (180) showed 63.67 ± 1.53% decrease in cellular oxidative stress which was the highest among all the tested compounds. WST cytotoxicity assay revealed the potency of hexane and ethyl acetate extract of M.latifolia towards KB cell line with half maximal inhibitory concentration (IC50) of 23.67 ± 1.53 and 36.37 ± 5.19 μg/mL respectively without showing significant toxicity towards the noncancerous cell lines whereas the new compound, amelicarin (176) showed poor selectivity with low IC50 in all cell lines. In conclusion, this study suggested the potential of C. excavata, M. minutum and M. latifolia as health promoting agents or as the sources of therapeutic alternatives.